Pengaruh Return On Investement Dan Debt To Equity Ratio Terhadap Harga Saham Pada PT. Clipan Finance Indonesia, Tbk - Prawira Aditiya Dzulfaden; Nurlinda; Nurwana; Maria Indang (Jurnal Online Manajemen ELPEI, 2023)
Effect of Return On Investment and Debt To Equity Ratio on stock prices at PT. Clipan Finance Indonesia, Tbk. This study aims to determine the effect of Return on investment and debt to equity ratio on stock prices at PT. Clipan Finance Indonesia,Tbk. The type of data used in this research is quantitative data. The data source used is secondary. The analytical method used at PT. Clipan Finance Indonesia in the 2022 period is a multiple linear regression analysis. From the results of the study, the results of multiple linear regression calculations obtained Y = 5.043 0.067X1 0.003X2. Correlation analysis correlation (R) of 0.911. Analysis of the coefficient of determination (R2) of 0.955. The results of the F test are Fcount 10.249 < Ftable 19.00 thus ROI and DER have a positive and insignificant effect on stock prices. Partially the ROI value is tcount (2.752 <4.303) while the DER value is tcount (3.753 <4.303) which means Ho is accepted and Ha is rejected. Therefore ROI and DER have a positive and insignificant effect on stock prices.Keywords: Return on investment, debt to equity ratio, stock price